Solve for x- 6 + 1 2 + 1 = 7 − 3 3​

Question

Solve for x-

6 + 1

2

+ 1 =

7 − 3

3​

in progress 0
Kinsley 2 months 2021-08-14T00:14:25+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-14T00:15:26+00:00

    Answer:


    ∴ x = -6


    Step-by-step explanation:


    x- 6+12 + 2 = 7-33


    or, x – 20 = – 26


    or, x = -26 + 20


    ∴ x = -6

    0
    2021-08-14T00:15:35+00:00

    Answer:

    ∴ x = -6

    Step-by-step explanation:

    x- 6+12 + 2 = 7-33

    or, x – 20 = – 26

    or, x = -26 + 20

    ∴ x = -6

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )